2006
DOI: 10.2527/jas.2005-667
|View full text |Cite
|
Sign up to set email alerts
|

Growth, reproductive performance, and manganese status of heifers fed varying concentrations of manganese1,2

Abstract: An experiment was conducted to examine the effects of dietary Mn on growth, reproductive performance, and Mn status of beef heifers. Eighty Angus (n = 40) and Simmental (n = 40) heifers, averaging 249 kg, were stratified by BW within a breed and randomly assigned to 1 of 4 treatments providing 0 (control), 10, 30, or 50 mg of supplemental Mn/kg of DM from MnSO(4). Heifers were individually fed a diet containing cottonseed hulls, corn gluten feed, citrus pulp, and ground corn, and the control diet contained 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 16 publications
5
44
2
Order By: Relevance
“…However, in a more recent study, it is reported that treating heifers with different concentrations of Mn did not affect the serum cholesterol (Hansen et al, 2006). This study indicates that even low serum levels of Mn are sufficient for cholesterol synthesis (Hansen et al, 2006). This result is quite consistent with our data of plasma cholesterol that showed no significant difference between the NC and the RB cows (Table 1).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…However, in a more recent study, it is reported that treating heifers with different concentrations of Mn did not affect the serum cholesterol (Hansen et al, 2006). This study indicates that even low serum levels of Mn are sufficient for cholesterol synthesis (Hansen et al, 2006). This result is quite consistent with our data of plasma cholesterol that showed no significant difference between the NC and the RB cows (Table 1).…”
Section: Resultssupporting
confidence: 83%
“…The earliest studies demonstrated that a manganese deficiency causes defective ovulation and subfertility of female and male (Tuormaa, 1996). It is suggested that Mn act as a cofactor for mevalonate kinase and farnesyl pyrophosphate synthase; enzymes involved in the production of squalene, a precursor of cholesterol (Davis et al, 1990;Hansen et al, 2006;Hidiroglou, 1979;Tuormaa, 1996;Watts, 1990). However, in a more recent study, it is reported that treating heifers with different concentrations of Mn did not affect the serum cholesterol (Hansen et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional status before slaughter can influence collagen content and its solubility and consequently meat tenderness (Thénard et al, 2006). Several studies investigated the effects of growth path and rate on carcass characteristics or meat quality in cattle (Jones et al, 1990;Hornick et al, 1998), but they were restricted to evaluation of the Longissimus muscle, regardless that compensatory growth effects on carcass and meat characteristics may be muscle-dependent (Hansen et al, 2006b). Consequently, results obtained in past studies cannot be extrapolated to the rest of the carcass.…”
Section: Introductionmentioning
confidence: 99%